PENGARUH METODE HYIPNOTECHING TERHADAP MOTIVASI BELAJAR SANTRI DI PONDOK PESANTREN MANGARAJA PANUSUNAN ACHIR HASIBUAN: Pengaruh Metode Hypnoteaching terhadap Motivasi Belajar Fikih Santri di Pondok Pesantren Mangaraja Panusunan Achir Hasibuan - nuryanti siregar; Rully Hidayatullah; Ahmad Muda Harahap; Nora Afnita; Sodikin Telambanua (Ikhtisar: Jurnal Pengetahuan Islam, 2026)
The learning process often makes students bored and tired, so it is important to have a learning approach that increases student learning motivation. This is especially true in fiqh learning that leads students to memorize a lot of learning material. The Hypnoteaching method is a learning approach that is considered effective in increasing student learning motivation. This learning approach emphasizes fun and interactive learning. This study aims to determine the effect of the hypnoteaching method on the motivation to learn fiqh in Islamic boarding school students. This study used an experimental method with a one-group pretest-posttest research design. The results of this study indicate that there is a significant effect of the use of the hypnoteaching method on the motivation to learn fiqh in Islamic boarding school students. This is evidenced by the results of the two-sample dependent t-test (paired-samples t-test), namely sig. 0.000 > 0.05. This indicates that the hypnoteaching method can increase the motivation to learn fiqh in Islamic boarding school students.